Nilai-Nilai Pendidikan Agama Islam dan Implementasinya dalam Menumbuhkembangkan Karakteristik Islami Peserta Didik - Wakidi; Aries Musnandar (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
PAI values ​​were applied in SMP PGRI 05 Tirtoyudo, Malang Regency. This was inseparable from the participation of teachers, school principals and parents. This study aimed to describe the program, the implementation, and the factors that affect the implementation of PAI values ​​in students in SMP PGRI 05 Tirtoyudo Malang Regency. The research design used was phenomenological method with a qualitative approach. The respondents consisted of PAI teachers, vice principal for student affairs,  school principals and students. Data collection used was observation, interviews and documentation. Data analysis included data collection, data condensation, data presentation, and conclusion/verification. The results show that the implementation of PAI values program ​​includes moral values, worship and muamalah. The program implementation is conducted in daily, weekly, monthly, annually, and incidental basis. The daily acivities include (greeting the teacher before entering the class, doing the Duha, doing the Duhur prayer, and praying at the beginning and the end of the lesson). The weekly activities include (wearing Muslim clothings every Friday, doing the Friday prayer and conducting the Friday infak). The monthly activites include (doing the istighotsah and spiritual recharging on Friday legi). The annual activities include PHBI and the incidental activities include (visiting the sick students and doing the takziyah when a family member dies). The factors that affect the implementation of PAI values ​​consist of internal factors (habits, awareness and motivation, students' ability to interact) and external factors (teacher’s exemplary, principal policy, parents, friends, facilities and infrastructure and the living environment)